Microscopic Interactions Between Different Block Ratios of Styrene–Butadiene–Styrene and Asphalt During Their Miscibility - Jinyang Deng; Yu Chen; Ke Cheng; Ning Xu; Jiaxin Chang; Gang Duan (CivilEng)
Styrene–butadiene–styrene (SBS)-modified asphalt is widely used in the field of road construction because it helps asphalt pavements achieve good road performance. However, SBS-modified asphalt has problems of poor compatibility, leading to insufficient thermal storage stability. As a block copolymer of styrene and butadiene, the compatibility of SBS with asphalt is also influenced by its styrene-to-butadiene (S/B) ratios. To reveal the compatibility mechanisms of different S/B ratios of SBS and asphalt during system stabilization, the interactions of SBS with asphalt at the molecular level were investigated in this study. Based on the molecular dynamics simulation method, interfacial models of SBS and asphalt were constructed; the miscible process of SBS in asphalt was simulated, with the characteristics of phase structure evolution and molecular distribution being analyzed; and the binding energy of the SBS/asphalt miscible systems was calculated. The results show that a higher butadiene content benefits the miscibility of SBS in asphalt and that the S/B ratios affect the interaction of SBS with asphalt and its components. SBS with a 3:7 ratio of styrene to butadiene exhibits stronger adsorption with the resin component and has the highest binding energy and best compatibility with asphalt. The findings contribute to the understanding of the miscibility and compatibility mechanisms between different S/B ratios of SBS and asphalt.